HUBUNGAN DUKUNGAN TEMAN SEBAYA DENGAN MINAT REMAJA PUTRI MINUM TABLET FE DI SMPN 2 SUKAPURA: The Correlation Between Peer Support and Young Girls' Interest in Drinking Fe Tablets at SMPN 2 Sukapura - Yenny Nilawati (ASSYIFA : Jurnal Ilmu Kesehatan, 2023)
The low interest of young women in consuming Fe tablets is one of the causes of nutritional anemia. This is because young women experience menstruation so they lose iron (Fe) and need more intake of iron (Fe). Peer support is included in the factors that can strengthen a person to behave. The correlation with peers are individual correlation that involve relatively large familiarity in the group. The purpose of this study was to analyze the correlation between peer support and the interest of young women to drink Fe tablets at SMPN 2 Sukapura. This study used a correlational analysis design with a cross-sectional approach. The sample data is a portion of the target youth at SMPN 2 Sukapura, a total of 60 young girls who meet the inclusion criteria using the cluster sampling technique. Data collection included coding, editing, and tabulating. Then the data were analyzed by computer with the Spearman test p-value: 0.05. The results showed that 53 respondents had supportive peers, 52 respondents had an interest in drinking Fe tablets and p-value: 0.000. There is a correlation between peer support and the interest of young women to drink Fe tablets (p = 0.000 <0.05). The suggestion put forward is that the youth health program holders at the Sukapura Health Center can advocate for schools to be able to provide policies/regulations for implementing nutritious actions in schools, by taking Fe tablets together once a week.